Improving functional outcomes and quality of life in an elderly woman with sarcopenia and spinal Tuberculosis: A case report - Defi, Irma Ruslina; Hamam, Nur Rusyidah; Biben, Vitriana; Al Barqi, Nuzula Chafidh (Frontiers in Rehabilitation Sciences, 2023)
Background: Indonesia is the world's second-largest contributor to TB patients. According to prevalence by age, the elderly have the most diagnosed TB. In Indonesia, TB spondylitis affects approximately 5% of TB cases and is a common cause of non-traumatic spinal cord injury (NTSCI). Spinal cord injury (SCI) is a growing public health concern, particularly among the elderly, as many of its populations have sarcopenia. Due to the complete absence of voluntary muscle contraction, SCI is followed by a rapid loss of skeletal muscle mass. SCI has several physical, psychological, social, and economic consequences. Case presentation: A 68-years-old woman presented with weakness and numbness of all four limbs. She also had sarcopenia, malnutrition, and dependency on activities of daily living (ADL). In addition, the patient was at a risk of SCI complications. Magnetic resonance imaging (MRI) showed destruction of the vertebral bodies at the level of the 5th and 6th cervical area, tuberculous abscesses of the paravertebral and longus colli muscles. The patient underwent debridement and spinal stabilization. However, the patient was at a risk of developing SCI complications. In these patients, the Physical Rehabilitation and Medicine (PRM) strategy focuses on improving medical conditions, including preventing secondary complications, promoting neurological recovery, and optimizing function. Conclusion: This case highlights the importance of PRM intervention in assessing functional disorders in the elderly to improve their quality of life (QOL).